Impact of cesarean section on transient tachypnea of the newborn: a longitudinal study - Joseph, Keziah; B., Bhargavi; Jain, C. S.; Reddy, Dasaradha Rami (International Journal of Contemporary Pediatrics, 2021)
Background: Transient tachypnea of the new born is a benign condition. The aim of the study is to find any correlation between the mode of delivery and occurrence of transient tachypnea of newborn. Methods: Study is proposed to assess the risk factor like caesarean section and its relationship with occurrence of TTN in term neonates and the clinical course of TTN cases admitted in Neonatal intensive care unit (NICU), Department of Pediatrics, Kamineni Institute of Medical Sciences, Narketpally, Nalgonda, Telangana. Results: During the study period, total number of deliveries in our hospital was 4576. Of 356 term neonates with respiratory distress admitted in NICU, the most common cause was found to be early onset sepsis i.e 168 of 356 cases accounting for 47.19%, followed by transient tachypnea of newborn i.e., 68 of 356 cases accounting for 19.10%. Conclusions: The mode of delivery i.e caesarean section has a significant impact on transient tachypnea of newborn (TTN) with a relative risk of 3.78 compared to normal vaginal delivery. The majority of cases had mild respiratory distress and were relieved of symptoms within 3 days of hospital stay.